Challenges to Effective Implementation of Integrated Disease Surveillance and Response Among Health Workers in Nigeria: A Systematic Review - Igho, Precious Oghenekome; Igunma, A Jeremiah (British Journal of Healthcare and Medical Research, 2023)
Introduction: With the high disease burden in most developing countries, especially in Africa, the integrated disease surveillance and response strategy was implemented in Nigeria to create an effective surveillance system. However, despite the adoption of the strategy, the desired goal has still not been met. Objective: This systematic review aimed to evaluate the challenges to effective implementation of IDSR among health workers in Nigeria. Methods: The study employed a systematic review of literature published in English with a focus on health workers in Nigeria. The search was conducted in databases, namely, PubMed, CINAHL, Advanced Google Scholar, Web of Science, and grey literature search. The PRISMA protocol was adopted for clarity in reporting, and quality appraisals were done using the MMAT tool. A total of 23 papers were included for the review, out of 2326 articles. The included articles focused on IDSR challenges among health workers in Nigeria and their recommendations for effective implementation. Results: Despite the high awareness noticed in the recent studies reviewed, there is low implementation of the strategy among health workers. The challenges faced by health workers, as shown by this review, were identified across all IDSR core and support functions. Low reporting due to lack of awareness and knowledge; lack of feedback and supervision; low case confirmation; lack of emergency preparedness unit; low laboratory capacity. Conclusion: Although the country has shown a lot of accomplishments since the implementation of IDSR, there are still obvious gaps in this implementation.